Choice, coercion, and/or muddling through: Older adults' experiences in seeking psychological treatment. (June 2020) - Berard, Lindsay D.H.; Mackenzie, Corey S.; Reynolds, Kristin A.; Thompson, Genevieve; Koven, Lesley; Beatie, Brooke
Abstract: Help-seeking related to mental health concerns has been found to decrease as age increases . Despite extensive literature devoted to barriers to accessing mental health services, the reasons why older adults are especially unlikely to seek treatment are not well understood. The present study had two objectives concerning the experiences of older adults accessing outpatient psychological treatment: 1) classifying pathways into treatment using the Network Episode Model (NEM; Pescosolido et al., 1998), and 2) critically examining whether these pathways effectively captured the process of seeking treatment for older adults. Utilizing secondary qualitative data from three studies (N = 35), we met our first objective of classifying pathways according to the NEM with directed content analysis. The majority (n = 21, 60%) of older adults willingly accessed treatment (choice) and 42.9% of those involved 'others' in their help-seeking by way of referrals or support. The remaining participants' (n = 14, 40%) pathways into treatment reflected a process of muddling through (being unsure of their need for mental health services and where to access support, or bouncing around the treatment system). No participants' pathways were categorized as coercive. To meet our second objective, we used conventional content analysis to explore how best to categorize pathways to treatment. Findings demonstrated that a minority of participants (n = 10, 28.6%) had a help-seeking journey that represented only one of the three pathways. Instead, most participants described a lengthy period of muddling through, eventually followed by a willingness to seek help. These findings highlight the complex process of seeking treatment, and suggest a need to implement more direct mental health literacy interventions to reduce the amount of time spent muddling through, while improving the experience of mental health help-seeking for older adults. Highlights: Mental health treatment seeking is a dynamic and social process. Older adults accessed mental health services willingly, often supported by others. Coercion was rare but most older patients "muddled through" treatment seeking. Increased mental health literacy and collaborative care is likely to improve treatment seeking.